One-year experience with ex vivo lung perfusion: Preliminary results from a single center. Issue 8 (August 2018) - Koch, Achim; Pizanis, Nikolaus; Olbertz, Carolin; Abou-Issa, Omar; Taube, Christian; Slama, Alexis; Aigner, Clemens; Jakob, Heinz G; Kamler, Markus
Objective: To enlarge the donor pool for lung transplantation, an increasing number of extended criteria donor lungs are used. However, in more than 50% of multi-organ donors the lungs are not used. Ex vivo lung perfusion offers a unique possibility to evaluate and eventually recondition the injured donor lungs. The aim of our study was to assess the enlargement of the donor pool and the outcome with extended criteria donor lungs after ex vivo lung perfusion. Patients and Methods: Data were prospectively collected in our lung transplant database. We compared the results of lung transplants after ex vivo lung perfusion with those after conventional cold static preservation. In total, 11 extended criteria donor lungs processed with ex vivo lung perfusion and 41 cold static preservation lungs transplanted consecutively between May 2016 and May 2017 were evaluated. Normothermic ex vivo lung perfusion was performed according to the Toronto protocol for 4 h. Cold static preservation lungs were stored in low-potassium dextran solution. Results: Ex vivo lung perfusion lungs before procurement had significantly lower PaO2 /FiO2 (P/F) ratios and more X-ray abnormalities. There were no statistically significant differences for pre-donation ventilation time, smoking history, or sex. After reconditioning with ex vivo lung perfusion, 9 out of 11 processed lungs were considered suitable and successfully transplanted. The mean postoperative ventilation time and in-hospital stay were not significantly different in ex vivo lung perfusion and cold static preservation recipients. Conclusion: Ex vivo lung perfusion can safely be used in the evaluation of lungs initially considered not suitable for transplantation. The primary outcome was not negatively affected and normothermic ex vivo lung perfusion is a useful tool to increase the usage of potentially transplantable lungs.